Comparison of the Anesthetic Effects of Tiletamine HCl– Zolazepam–Xylazine and Ketamine–Diazepam–Xylazine in Older Foals under Field Conditions - Phutthachalee, Suphannika; Cherdchutham, Worakij; Laikul, Aree; Phetudomsinsuk, Kanittha; Chanda, Metha; Phukudom, Sukumal (Agriculture and Natural Resources, 2012)
The purpose of the study was to compare the drug combinations effect of xylazine–tiletamine HCl–zolazepam (XZ group) and xylazine–ketamine–diazepam (XKD group). Both drug groups were administered to six older foals, with ages ranging from 4 to 6 mth and body weight between 107 to 125 kg in a crossover design. Measured parameters were heart rate, respiratory rate, body temperature, blood glucose, systolic and diastolic blood pressure, mean arterial blood pressure and blood gas variables (pH, PaO2, PaCO2, HCO3, TCO2, BE, and saturated oxygen (SaO2). All parameters were evaluated at 5 min before and 7 min after administering xylazine and were also measured at 5, 10, 15 and 20 min after the administration of the anesthetic drugs. The quality of induction and recovery, quality of mouth opening and intubation, number of attempts to regain sternal recumbency, standing position and duration of anesthetic effects were measured. There were no signiﬁ cant (P > 0.4) differences in any measured parameters of both drug groups suggesting that the xylazine – tiletamine HCl–zolazepam combination was safe for anesthetic induction in older foals.